Effect of dietary supplementation with Moringa oleifera leaf extract and Lactobacillus acidophilus on growth performance, intestinal microbiota, immune response, and disease resistance in whiteleg shrimp (Penaeus vannamei). Issue 127 (August 2022) - Abidin, Zaenal; Huang, Huai-Ting; Hu, Yeh-Fang; Chang, Jui-Jen; Huang, Chih-Yang; Wu, Yu-Sheng; Nan, Fan-Hua
Abstract: This study investigated the effect of the moringa ( Moringa oleifera ) leaf extract and Lactobacillus acidophilus individually or combined on growth performance, enzyme activity, intestinal and hepatopancreatic histology, intestinal microbiota, immune response, and resistance against Vibrio alginolyticus and Vibrio parahaemolyticus in whiteleg shrimp ( Penaeus vannamei ). Six diets were formulated: three diets without L. acidophilus containining 0 (control, ME0), 2.5 (ME2.5), and 5. 0 g/kg of moringa (ME5.0) and the same three diets containing L. acidophilus at 1 × 10 7  CFU/g of diet (ME0+P, ME2.5 + P, and ME5.0 + P, respectively). Growth performance was measured after 60 days of the rearing period. On the final day, the shrimp were sampled to assess enzyme activity, intestinal and hepatopancreatic histology, and gut microbiota. Shrimp hemocytes were examined on Days 0, 1, 2, 4, 7, 14, 21, and 28 to measure the immune response in terms of the total hemocyte count, phenoloxidase activity, phagocytosis, and superoxide anion production. Furthermore, the shrimp were challenged with V. alginolyticus and V. parahaemolyticus . The results revealed that ME2.5 + P significantly increased ( P  < 0.05) final weight, weight gain, specific growth rate, enzyme activities, and villi height compared with ME2.5 and control. Wall thickness was increased in the shrimp fed diet supplemented with moringa and L . acidophilus compared with the control shrimp. Hepatopancreatic histology revealed that R cells were more abundant in the shrimp fed diet containing moringa and L. acidophilus compared with those fed diet containing moringa alone ( P  < 0.05) at the same concentration. High-throughput sequencing analysis indicated that the dietary supplementation with moringa and L. acidophilus affected the gut microbiota composition. All gene functions, members of KEGG level 2, related to metabolism were increased in diet supplemented with moringa with or without L. acidophilus compared with the control group. The immune assay revealed that the total hemocyte count, phenoloxidase activity, phagocytic rate, superoxide anion production, and immune-related gene expression (including those of prophenoloxidase II, alpha-2-macroglobulin, penaeidin2, antilipopolysaccharide factor, crustin, lysozyme, glutathione peroxidase, and superoxide dismutase) were higher in the experimental groups than in the control group on several observed days; however, the increases were observed more often in the ME2.5 + P group than in the other treatment groups. Furthermore, the ME2.5 + P group exhibited a significantly higher survival rate ( P  < 0.05) in the challenge test against V. alginolyticus and V. parahaemolyticus. In conclusion, supplementation with dietary moringa and L. acidophilus at ME2.5 + P improved growth performance, immune system, and resistance against Vibrio in the shrimp. Highlights: Moringa and L. acidophilus improve the growth and immunity of whiteleg shrimp. Moringa and L. acidophilus have a beneficial effect on intestine and hepatopancreas morphology, and enzyme activities. Moringa and L. acidophilus modulate intestinal microbiota and the gene functions. Moringa and L. acidophilus enhance the resistance against the V. algynolyticus and V. parahaemolyticus .